Federal Sentencing Guidelines and United States v. Booker: Social Context and Sentencing Disparity - Nowacki, Jeffrey S. (Criminal justice policy review, 2018)
The United States v. Booker decision rendered Federal Sentencing Guidelines advisory rather than mandatory. In the context of this decision, this study examines both the direct influence of aggregate-level political, community, and administrative variables on sentencing outcomes, and the way that such characteristics might contextualize individual-level predictors. Using multi-level regression techniques, this study examines the role of aggregate-level variables on sentence length decisions across four distinct time periods. Moreover, this article also examines whether aggregate-level variables condition the effects of race/ethnicity on sentencing outcomes. Whereas the direct effects of aggregate-level variables on sentencing outcomes are generally limited to political climate effects, there is evidence that political climate and other aggregate-level measures contextualize individual-level race/ethnicity effects. Future research should seek to better understand the specific mechanisms behind these relationships.